Kinetika reaksi esterifikasi palm fatty acid distilate (PFAD) menjadi biodiesel dengan katalis zeolit-zirkonia tersulfatasi - Masduki Masduki; Sutijan Sutijan; Arief Budiman (Jurnal Rekayasa Proses, 2013)
Energy crisis due to depletion of crude oil resources has been a motivation for alternative energy search. Biodiesel becomes a potential among other alternative energy sources. However, large scale biodiesel production is hampered by the raw materials which become expensive and tent to compete with the source of food needs. Therefore, a search for an alternative inexpensive raw material is necessary. Palm fatty acid distilate (PFAD) is one of alternative raw materials can be utilized. The present work objective was to investigate reaction kinetics of PFAD esterification for biodiesel with zirconium sulphated zeolite as catalyst.PFAD as a source of fatty acid underwent esterification to produce biodiesel in a three necked flask equiped with heater, stirrer and reflux condensor. In order to study the reaction kinetics, samples were collected consecutively every 10 minutes and the conversion of the fatty acid in each sample was determined. Here, two esterification reaction models were proposed i.e. pseudo-homogeneous first order reaction model and heterogeneous catalytic reaction model.The results showed that calculated conversion for both proposed models were in a good agreement with the experimental data. The pseudo homogeneous reaction model has an activation energy of 11.60 kJ/mole and a pre-exponential factor of 5.82×1016 s-1. Whereas, the heterogeneous reaction model has an activation energy of 950.46 kJ/mole and pre-exponential factor of 4.11×1010 dm6.g cat-1.mol-1.s-1. The maximum conversion of 75.68% was obtained at 80 minute reaction time, at 65°C with the use of 3% catalyst and a PFAD:methanol molar ratio of 1:10.